2014
DOI: 10.1088/0004-637x/785/1/42
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of Massive Dense Cores Down to ≲ 1000 Au: Relation Between Fragmentation and Density Structure

Abstract: In order to shed light on the main physical processes controlling fragmentation of massive dense cores, we present a uniform study of the density structure of 19 massive dense cores, selected to be at similar evolutionary stages, for which their relative fragmentation level was assessed in a previous work. We inferred the density structure of the 19 cores through a simultaneous fit of the radial intensity profiles at 450 and 850 µm (or 1.2 mm in two cases) and the Spectral Energy Distribution, assuming spheric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
138
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(159 citation statements)
references
References 100 publications
21
138
0
Order By: Relevance
“…As in M 16, these α values have to be taken with caution since they mix different structures. Nevertheless, the high alpha value observed in regions close to the ionizing sources has already been seen in other regions such as the central, dense, high-mass starforming ridge in the cloud NGC 6334 (Russeil et al 2013) and more recently in Palau et al (2014) for the massive dense cores DR21-OH, AFGL 5142 and CB3. The transition from high values to low values typical of other clouds seems to indicate that the compression from ionization is also playing a role at high column densities where structures are expected to be gravitationally collapsing.…”
Section: Rosette Nebulamentioning
confidence: 76%
“…As in M 16, these α values have to be taken with caution since they mix different structures. Nevertheless, the high alpha value observed in regions close to the ionizing sources has already been seen in other regions such as the central, dense, high-mass starforming ridge in the cloud NGC 6334 (Russeil et al 2013) and more recently in Palau et al (2014) for the massive dense cores DR21-OH, AFGL 5142 and CB3. The transition from high values to low values typical of other clouds seems to indicate that the compression from ionization is also playing a role at high column densities where structures are expected to be gravitationally collapsing.…”
Section: Rosette Nebulamentioning
confidence: 76%
“…In the following, we investigate the effects of turbulent and thermal pressure in regulating the fragmentation of the clusters in NGC 6334, by determining the Jeans mass and comparing with the measured mass of the fragments (see e.g. Palau et al 2015Palau et al , 2014.…”
Section: Fragmentation Statusmentioning
confidence: 99%
“…Furthermore, these simulations suggest that the initial density profile of star-forming clumps/cores could be the most important factor for fragmentation and evolution of HMSF regions. Palau et al (2014) observed a number of massive dense cores to study the relation between fragmentation and density structure of massive cores and they find that steeper density profiles tend to show lower fragmentation. These results probably indicate that AS more easily form massive stars by limiting fragmentation.…”
Section: Massive Star Formationmentioning
confidence: 99%